Clinical, Enamel, and Radiographic Features of Amelogenesis Imperfecta in Pediatric Patients: A Multicenter Study - Hyemin Yin; Hyuntae Kim; Ji-Soo Song; Teo Jeon Shin; Hong-Keun Hyun; Young-Jae Kim; Jung-Wook Kim (THE JOURNAL OF THE KOREAN ACADEMY OF PEDTATRIC DENTISTRY, 2026)
This study aimed to characterize the clinical, enamel, and radiographic features of amelogenesis imperfecta (AI) in pediatric patients in Korea and to compare these features across AI phenotypes. This multicenter retrospective study reviewed records of 39 patients aged < 18 years who were diagnosed with AI across 11 university dental hospitals between 2022 and 2025. The patients were classified into hypoplastic, hypomaturation, and hypocalcified phenotypes according to the Witkop classification. The clinical, enamel, and radiographic variables were collected using a standardized electronic case report form, and the differences among the phenotypic groups were analyzed using the Monte Carlo version of Fisher’s exact test. The hypoplastic phenotype was the most prevalent (53.8%), followed by hypomaturation (28.2%) and hypocalcified (17.9%). The mean age at first dental visit was 9.62 ± 3.48 years, with most patients presenting during the mixed or permanent dentition stage. Hypersensitivity, periodontal disease, and crossbite differed significantly by phenotype and were most frequent in the hypocalcified group. The hypoplastic group most frequently showed white-yellow discoloration, pitting, and reduced radiographic enamel thickness, whereas the hypocalcified group showed yellow-brown discoloration, enamel wear, and decreased radiopacity in all cases. Taurodontism was the most frequently identified radiographic anomaly. This multicenter cohort study suggests phenotype-related differences in the clinical manifestations of AI and provides baseline clinical information that may support earlier diagnosis and inform phenotype-based multidisciplinary management in pediatric patients.